Falls and fall-related injuries: prevalence, characteristics, and treatment among participants of the Geelong Osteoporosis Study - Tewodros Yosef; Tewodros Yosef; Julie A. Pasco; Julie A. Pasco; Julie A. Pasco; Monica C. Tembo; Lana J. Williams; Kara L. Holloway-Kew (Frontiers Media S.A., 2024)
BackgroundFalls are a significant public health challenge, especially among older adults. In Australia, falls and related injuries incur an annual cost of $2.3 billion. However, there is a scarcity of prevalence data on falls among population-based groups. This study aimed to report the characteristics, circumstances, and treatment for falls and fall-related injuries in a population-based sample of Australian men and women.MethodsParticipants from the Geelong Osteoporosis Study provided cross-sectional data: baseline for men (2001-2006) and 10-year follow-up for women (2004-2008). Falls over the previous 12 months were self-reported by 2,631 participants aged 20-97 years (1,533 men and 1,098 women). The study described the timing, location, cause, and treatment of falls. Fall prevalence was standardized to the 2006 Australian population. Data collection included self-reported prior fractures, medication, disease conditions, anthropometry, and biochemical tests. Binary logistic regression identified factors linked to fall-related injuries.ResultsFall rates by age group: 20-29 (24.4%), 30-39 (21.5%), 40-49 (18.7%), 50-59 (24.9%), 60-69 (25.0%), 70-79 (34.6%), 80+ (40.5%). The age-standardized prevalence of falls was 25.0% (95% CI: 23.4-26.7%). In adults ≥65 years, the age-standardized prevalence of falls was 32.4% (95% CI: 29.3-35.5%). Fallers were typically older, less mobile, had higher BMI and cholesterol levels, and were more likely to have musculoskeletal conditions, cancer, and polypharmacy. Men had a higher fall risk, but fewer fall-related fractures compared to women. Most falls occurred outdoors (62.1%), were due to extrinsic cause (58.5%), and were on the same level (78.5%). Factors associated with fall-related injuries included being female, elevated falls and falls outside the home. Nearly half (45.7%) of those injured sought medical attention, primarily from general practitioners (25.7%) and emergency departments (12.6%).ConclusionFalls are common, occurring in approximately one quarter of adults in this study, with a greater prevalence among those ≥65 years. Women experienced fewer multiple falls than men. Many participants sought medical attention, primarily from general practitioners. This research identifies fall characteristics and circumstances, informing targeted prevention strategies to reduce occurrences and alleviate burdens on healthcare systems and individuals.